A Perfectly Symmetrical Configuration in Dual-Bridge Inverter Topology for Maximum Mitigation of EMI, Common-Mode Voltages and Common-Mode Currents - Akroum, H.; Kidouche, M.; Grouni, S.; Zelmat, M. (Elektronika ir Elektrotechnika, 2010)
The paper shows some of the most notable difficulties connected with constructing a superconducting magnets frequency characteristics test system. The hardware and software of the system was shown, and the method of calculating the model of the magnet coil parameters. The paper shows some of the test results of example superconducting magnets.